BAHASA ANCAMAN DALAM TEKS KABA SABAI NAN ALUIH BERBASIS PENDEKATAN LINGUISTIK FORENSIK - Wahyudi Rahmat (JURNAL ARBITRER, 2015)
This thesis is focused on the analysis threat language in Kaba Sabai Nan Aluih text. The aims of this thesis are to explain the form, meaning and motive of threaten language by employing several theory, including Searle (1969) and Wijana (1996), Aminuddin (2008) to figure out the meaning, while the motive form used the theory stated by Maslow (1943). The research is conducted by using observational method along with the techniques. In analyzing the data use distributional and identity method. Identity method that employs including reference and pragmatic identity method while in distributional method employs marker identification techniques. The result of analysis is presented in informal method. These method and techniques are identical with proposed by Sudaryanto (1993) and Mastoyo (2007). The result of the analysis shows that there are four types of language threat form; (1) direct speech act, (2) indirect speech act, (3) literal speech act, and (4) non literal speech act. The meaning of threaten language in KSNA are (1) think in every act, because if it is not doing so would cause harm to themselves; (2) pride and arrogance will lead to the destruction of those who have the attitude; (3) every person should have a sense of caring so that the people closest to us are not wrong in its attitude and decisions; (4) a form of error should be fixed even if the truth is painful; (5) is a self-esteem is everything, (6) to save themselves with a threats speech can be used if someone was in danger of being defeated; (7) not all forms of threat is a detrimental thing; (8) awaken the nearest fault has been done is a form of responsibility; (9) threatening to a motivation not an adverse thing; (10) awaken people closest guilt is a form of right action; (11) fixed price for an appropriate fee for the self-esteem that has been tarnished, and (12) very uncontrolled emotion can cause harm. The motive of threat language in KSNA are (1) dissatisfaction, (2) test of the intelligence, (3) pain, (4) displeasure of the attitude of a person, (5) self-esteem, (6) revenge, (7) self defended mechanism by using threat, (8) motivation, (9) mocking in order to direct people to do something, (10) sarcasme to boost spirit, (11) revenged, (12) motif of self defended, (13) grief. Â  Keywords: KSNA , threats form, threats meaning, threats motive